Down-Syndrome-Related Maternal Dysbiosis Might Be Triggered by Certain Classes of Antibiotics: A New Insight into the Possible Pathomechanisms - Gábor Ternák; Gergely Márovics; Katalin Sümegi; Zsolt Bánfai; Gergely Büki; Lili Magyari; András Szabó; Béla Melegh (MDPI AG, 2023)
Down syndrome (DS) is a leading human genomic abnormality resulting from the trisomy of chromosome 21. The genomic base of the aneuploidy behind this disease is complex, and this complexity poses formidable challenges to understanding the underlying molecular basis. In the spectrum of the classic DS risk factor associations, the role of nutrients, vitamins, and, in general, the foodborne-associated background, as part of the events ultimately leading to chromosome nondisjunction, has long been recognized as a well-established clinical association. The integrity of the microbiome is a basic condition in these events, and the dysbiosis may be associated with secondary health outcomes. The possible association of DS development with maternal gut microbiota should therefore require more attention. We have hypothesized that different classes of antibiotics might promote or inhibit the proliferation of different microbial taxa; and hence, we might find associations between the use of the different classes of antibiotics and the prevalence of DS through the modification of the microbiome. As antibiotics are considered major disruptors of the microbiome, it could be hypothesized that the consumption/exposure of certain classes of antibiotics might be associated with the prevalence of DS in European countries (N = 30). By utilizing three different statistical methods, comparisons have been made between the average yearly antibiotic consumption (1997-2020) and the estimated prevalence of people living with DS for the year 2019 as a percentage of the population in European countries. We have found strong statistical correlations between the consumption of tetracycline (J01A) and the narrow-spectrum, beta-lactamase-resistant penicillin (J01CF) and the prevalence of DS.